Assessment of price and nutritional quality of gluten-free products versus their analogues with gluten through the algorithm of the nutri-score front-of-package labeling system. Issue 10 (20th April 2021) - De las Heras-Delgado, Sara; Alías-Guerrero, Adoración de las Nieves; Cendra-Duarte, Esther; Salas-Salvadó, Jordi; Vilchez, Elisenda; Roger, Esther; Hernández-Alonso, Pablo; Babio, Nancy
Abstract : This is the first study comparing the nutritional quality between gluten-free products and their analogues with gluten using the FSAm/HCSP nutrient system underlying the Nutri-Score label. Abstract : Evidence has shown that the nutritional quality of gluten-free products (GFPs) is lower than that of non-GFPs. Our main objective was to compare the nutritional quality through nutritional profiles of foods underlying the Nutri-Score front-of-pack and the price of GFPs with respect to non-GFPs, and to evaluate whether there is a correlation between both parameters. Nutritional information of all products was obtained from the CELIACBASE database and the price through Spanish supermarkets websites. Global quality using the Nutri-Score algorithm and the price were compared between both types of products. GFPs do not always have poorer quality than their counterparts. A better quality of gluten-free pasta was correlated with the higher price but also a worse quality of gluten-free muesli was correlated with the higher price. The price of GFPs compared to non-GFPs was higher up to 391.5%. However, for ham and cheese pizza, ham pizza, Marie biscuits, and baby biscuits, the difference was not statistically significant. Generally, the price of GFPs did not correlate with better nutritional quality. Nutri-Score would ease the nutritional quality identification, empowering consumers and could also influence manufacturers to improve the nutritional quality of GFPs. Nowadays, given that many GFPs have poor nutritional quality, they should be included only occasionally in a balanced gluten-free diet.